2019
DOI: 10.1186/s40623-019-1068-9
|View full text |Cite
|
Sign up to set email alerts
|

Special issue “Towards forecasting phreatic eruptions: examples from Hakone volcano and some global equivalents”

Abstract: which permits unrestricted use, distribution, and reproduction in any medium, provided you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Phreatic eruptions do not expel juvenile magma and are typically small in scale. For "wet volcanoes" they can be the dominant type of volcanic eruption that sometimes causes hazardous damage (e.g., Caudron et al, 2015;Yamaoka et al, 2016;Mannen et al, 2019). Although understanding the mechanism and forecast of phreatic eruptions are still challenging, previous studies have shown that various processes in magma-hydrothermal systems, such as rapid pressurization of fluids due to contact between groundwater and hot rocks, increased release of magmatic gases, rapid vaporization of superheated water due to decompression, and sealing by precipitation of hydrothermal minerals, play an important role in triggering this type of eruption (e.g., Hedenquist and Henley, 1985;Barberi et al, 1992;Mastin, 1995;Browne and Lawless, 2001;Stix and de Moor, 2018;Ohba et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Phreatic eruptions do not expel juvenile magma and are typically small in scale. For "wet volcanoes" they can be the dominant type of volcanic eruption that sometimes causes hazardous damage (e.g., Caudron et al, 2015;Yamaoka et al, 2016;Mannen et al, 2019). Although understanding the mechanism and forecast of phreatic eruptions are still challenging, previous studies have shown that various processes in magma-hydrothermal systems, such as rapid pressurization of fluids due to contact between groundwater and hot rocks, increased release of magmatic gases, rapid vaporization of superheated water due to decompression, and sealing by precipitation of hydrothermal minerals, play an important role in triggering this type of eruption (e.g., Hedenquist and Henley, 1985;Barberi et al, 1992;Mastin, 1995;Browne and Lawless, 2001;Stix and de Moor, 2018;Ohba et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of the presence of shallow magma, flashed water contains enough energy to efficiently fragment rock and violently eject material upwards and laterally (Montanaro et al., 2016a; Morgan et al., 2009). Often impulsive and short‐lived relative to magmatic eruptions, they are still deadly due to their sudden onsets, and the generation of violent blasts (Breard et al., 2014; Hurst et al., 2014; Kaneko et al., 2016; Mannen et al., 2019). For instance, the unheralded 2014 Ontake eruption in Japan (Yamamoto, 2014), and the 2019 Whakaari (White Island) eruption in New Zealand (Kennedy et al., 2020) resulted in ∼100 combined fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…A phreatic eruption results from the vaporization of fluids located at shallow depths beneath a volcano. Such vaporization is often triggered by the intrusion of magmatic fluid, which is sometimes detectable in well-monitored volcanoes (Yamaoka et al 2016;Mannen et al 2019). However, in many cases, there are long time lags between an intrusion of the magmatic fluid and the subsequent phreatic eruption (Stix and De Moor 2018).…”
Section: Introductionmentioning
confidence: 99%